2015
DOI: 10.3989/loquens.2015.024
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus: mechanisms, measures and sound treatments

Abstract: Tinnitus is the auditory perception of sounds in the absence of any external source. Tinnitus that occurs every day for more than five minutes is reported by 10-15% of the population, and for 1 to 2% it is a handicap that interferes significantly with their quality of life (severe tinnitus). Despite the intensive research into therapeutic options, including surgery, pharmacotherapy, and electrical and acoustical stimulation, there is no approved treatment for tinnitus at present. Although the exact origin of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…Tinnitus is one of the most common complaints in otorhinolaryngology and audiology outpatient clinic, and is usually classified as subjective and objective tinnitus. Epidemiological studies have shown that it can affect approximately 10–15% of adults [ 1 , 2 ], leading to serious impact on quality of life [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tinnitus is one of the most common complaints in otorhinolaryngology and audiology outpatient clinic, and is usually classified as subjective and objective tinnitus. Epidemiological studies have shown that it can affect approximately 10–15% of adults [ 1 , 2 ], leading to serious impact on quality of life [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tinnitus is the conscious perception of sound heard in the absence of physical sound sources external or internal to the body (Eggermont & Tass, 2015). Epidemiological studies report that tinnitus roughly affects 10 % of the adult population (Hall et al, 2015) and severely disturbs the quality of life of about 1-2 % of adults by producing anxiety, annoyance, irritability, disturbed sleep patterns, and depression (Cobo, 2015;Diges, Simón, & Cobo, 2017;Van de Heyning et al, 2007;Vio & Holme, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…En el caso auditivo, un déficit de la entrada periférica se puede producir por pérdidas auditivas (hipoacusia) debidas a sobreexposición a ruido, envejecimiento, o cualquier otra causa. Esta pérdida de información auditiva periférica puede originar diferentes mecanismos de compensación plástica a nivel sub-cortical y cortical, incluyendo (Cobo, 2015;Eggermont, 2012):…”
Section: Introductionunclassified
“…Cuando el acúfeno cursa con ansiedad y/o depresión, los ansiolíticos y/o antidepresivos pueden ayudar a reducir los síntomas emocionales. Por suerte, han proliferado muchas terapias que pueden proporcionar alivio del acúfeno (Cobo, 2015). Muchas de ellas combinan alguna terapia sonora para disminuir la señal del acúfeno con el consejo médico para desactivar sus reacciones negativas (Jastreboff, 2015).…”
Section: Introductionunclassified